Differential Downregulation of E-Cadherin and Desmoglein by Epidermal Growth Factor - Miquella G. Chavez; Christian A. Buhr; Whitney K. Petrie; Angela Wandinger-Ness; Donna F. Kusewitt; Laurie G. Hudson (Dermatology Research and Practice)
Modulation of cell : cell junctions is a key event in cutaneous wound repair. In this study we report that activation of the epidermal growth factor (EGF) receptor disrupts cel : cell adhesion, but with different kinetics and fates for the desmosomal cadherin desmoglein and for E-cadherin. Downregulation of desmoglein preceded that of E-cadherin in vivo and in an EGF-stimulated in vitro wound reepithelialization model. Dual immunofluorescence staining revealed that neither E-cadherin nor desmoglein-2 internalized with the EGF receptor, or with one another. In response to EGF, desmoglein-2 entered a recycling compartment based on predominant colocalization with the recycling marker Rab11. In contrast, E-cadherin downregulation was accompanied by cleavage of the extracellular domain. A broad-spectrum matrix metalloproteinase inhibitor protected E-cadherin but not the desmosomal cadherin, desmoglein-2, from EGF-stimulated disruption. These findings demonstrate that although activation of the EGF receptor regulates adherens junction and desmosomal components, this stimulus downregulates associated cadherins through different mechanisms.